Investment manager analysis : - Travers, Frank J. (John Wiley & Sons, 2004)
Investment Manager Analysis provides readers with a broad framework that covers the investment manager due diligence process from initial screening to analytical techniques, interviewing skills, and legal and contract negotiations. As it guides the reader through the selection process, it clearly demonstrates a variety of mechanisms for monitoring and tracking investment managers and the underlying investment portfolios.